2015
DOI: 10.1371/journal.pone.0140021
|View full text |Cite
|
Sign up to set email alerts
|

Current Prevalence Pattern of Hypertension in Nigeria: A Systematic Review

Abstract: BackgroundThe global burden of hypertension and other non-communicable diseases (NCDs) is rapidly increasing, and the African continent seems to be the most affected region in the world. The prevalence of hypertension in Nigeria forms a substantial portion of the total burden in Africa because of the large population of the country currently estimated to be over 170 million.ObjectiveThe purpose of this systematic review is to summarise up to date data on the prevalence and distribution of hypertension in Niger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
117
13

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(166 citation statements)
references
References 57 publications
20
117
13
Order By: Relevance
“…However, the observed prevalence rate falls within the documented prevalence rate of adolescent hypertension of 0.1to 17.5% in Nigerian adolescents. 4,11,[24][25][26] …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the observed prevalence rate falls within the documented prevalence rate of adolescent hypertension of 0.1to 17.5% in Nigerian adolescents. 4,11,[24][25][26] …”
Section: Discussionmentioning
confidence: 99%
“…10 A recent systematic review of studies done in the last 2 decades on the prevalence of hypertension in Nigeria, reported a crude prevalence range of 2.1% to Hypertension and its correlates among in-school adolescents in Ekiti State, South-west, Nigeria 47.2% for hypertension in adults and 0.1 to 17.5% for hypertension in children and adolescents. 4,11 In most studies, prevalence of hypertension was higher in males than females, similarly, the prevalence was higher in urban than rural areas. 11 Studies have shown that the earlier the age of onset of hypertension, the more likely that the affected individual will develop complications if not well treated.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In Nigeria, a neighborhoods country, the prevalence of hypertension among adults fluctuated from 2.1% to 47.2% in a sample of 400 participants [8], whereas in Ghana the prevalence of pre-hypertension and hypertension was 30.7% and 42.4%, respectively in a sample of 6,000 participants [9]. In a sample of 1,431 participants aged 18 years or older, the study older [10].…”
mentioning
confidence: 91%
“…Studies in Nigeria on Knowledge and risk factors of NCDs have focused on specific NCDs like hypertension, obesity, diabetes etc knowledge and risk factors [16][17][18][19][20][21]. Only a few studies on the knowledge and prevalence of the behavioral risk factors contributing to NCDs among the general population have been undertaken.…”
Section: Introductionmentioning
confidence: 99%